Saberes ancestrales del sobanderismo como atractivo cultural montubio - Rivera Morales, Jerry David (2021)
The development of the case study is aimed at describing the ancestral montuvian knowledge "Sobanderismo" to promote it as a cultural attraction of ethno-tourism, today in the Province of Los Ríos there are some places that still carry out this activity maintain this tradition that has been taught from their ancestors, these sites will also be made known to national and foreign tourists so that they can visit it. The results achieved from the project through the interviews and the registration form made it known that the Sobanderos would be willing to create an association so that national and foreign tourists can learn these montuvian cultural practices and thus ethno-tourism can be promoted. Through the information obtained, such as the definition of sobanderism, it will be possible to obtain a clearer way of what this ancestral practice consists of and where this activity occurs in the province of Los Ríos so that tourists visit the places and thus have a national tourist influx. and extracted.